Antecedents of Instapoetry: Considering the Commercial Short Form Aphorism Before and Beyond the Social Media Sphere - James Mackay; Polina Mackay (European Journal of American Studies)
Instapoetry is a form of short-form poetry that has gained immense popularity in the past decade, and has until now been particularly associated with digital culture. We argue that the success of this form owes much to publishers recognizing the growing cultural obsession with self-empowerment and personal trauma healing, and meeting this demand with mass-produced commercial products. The major Instapoets should, therefore, be separated from the mass of social media poetry, and instead be considered as professional writers producing content for this self-care publishing industry. Instapoetry’s lack of metrical control or linguistic complexity can be attributed to consumer preferences for short-form commercial aphorisms that can appeal to a wide audience. We suggest that broader consideration should be given to previous iterations of commercial short-form aphorisms, such as those found in postcards, greetings cards and novelty items like motivational posters, to better understand the cultural significance of Instapoetry.